Efecto de polinización asistida y poda de hojas en el rendimiento de palma aceitera (Elaeis guineensis Jacq ) en la empresa “Palmas del Shanusi” Loreto - Yurimaguas - Saavedra Castillo, Richard Fernando (2012)
This research paper entitled "Effect of assisted pollination and pruning of leaves on the performance of oil palm (Elaeis guinensis Jack), had the following objectives: To evaluate the effect of the frequency of assisted pollination in plants of 27 months from planting, in the performance of fresh fruit bunches (FFB) in Business "Palmas del Shanusi" Yurimaguas - Loreto, assess the effect of leaf pruning on yield of fresh fruit bunches (FFB) of oil palm Palmas del Shanusi company and performing economic analysis assisted pollination and leaf pruning on yield of fresh fruit bunches (FFB). This work was carried out in the Company "Palmas del Shanusi, politically located in the Province of Alto Amazonas Yurimaguas, we used the design of randomized complete block with factorial 2 for three, involving two and three frequencies of pollination types of pruning and had a duration of one year, which included the February 1, 2001 to February 1, 2012. The results indicate that the higher frequency of assisted pollination greater the number of pollinated female inflorescence at anthesis. The frequency of F2 assisted pollination (3 times / week) was assisted pollination frequency that is more pollinated female inflorescences (average 1916.2) compared with the frequency of F1 assisted pollination (2 times / week) with averages of 1374.5 respectively. Regarding the emission foliar statistically similar results were obtained with respect to frequency F1 assisted pollination (2 times / week) and F2 (3 times / week) with an average of 2.54 leaves per month and with respect to the sheet pruning P1 (40 sheets = 5 cable) P2 (36 sheets = 4.5 spirals) and P3 (32 sheets= 4 spirals) statistically similar results were obtained with 2.5, 2.6 and 2.5 leaves per month respectively. The treatments T6 (F2P3) involving pollination frequency 3 times a week and type of pruning spiral 32 sheets = 4 T4 (F2P1) involving pollination frequency 3 times a week and type of pruning 40 sheets = 5 cable and T5 (F2P2) involving pollination frequency 3 times a week and type of pruning of 36 sheets = 4.5 spirals statistical results were similar with respect to profitability with 293.97, 285.86 and 266.71 respectively, with respect to T1 (F1P1) pollination involving frequency 2 times a week and type of pruning espiralesT2 40 sheets = 5 (F1P2) involving pollination frequency 2 times a week and type of pruning of 36 sheets = 4.5 spirals and T3 (F1P3) involving pollination frequency 2 times a week and type of pruning of 32 sheets = 4 spirals with low averages of 213.37, 220.31 and 222.39 respectively. In general the effect of assisted pollination frequency of 3 times a week, strongly influenced by the number of inflorescences pollinated, harvested number of bunches and the weight of bunches with respect to the frequency of assisted pollination 2 times per week.